O papel do crédito rural e da infraestrutura de transportes para o desenvolvimento da agricultura brasileira - Márcio Bruno Ribeiro; Júnia Cristina Péres Rodrigues da Conceiç\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This study aimed to verify the relationship for the period 1999-2015 among Brazilian agricultural gross domestic product (GDP), rural credit and transport infrastructure investment. For this purpose, the time series methodology was applied to quarterly data, involving an estimation of a vector error correction model (VECM) and Granger causality tests. The results of the estimation of VECM suggest a negative long run relationship from public infrastructure investment to rural credit and agricultural GDP, but with a low economic impact. Granger tests pointed causality from agricultural GDP to rural credit and public infrastructure investment, and from agricultural GDP and public investment to credit. These results suggest that agricultural GDP growth had the potential to leverage the demand for rural credit and infrastructure investments. On the other hand, the competition for resources between financing rural production and public infrastructure investment resulted in a negative impact on the agricultural sector in the long run.
Keywords: Q10; Q18; 330; rural credit; transport infrastructure; agricultural gross domestic product